Calcareous algae, foraminifera and sequence stratigraphy of the Fahliyan Formation at Kuh-e-Surmeh : (Zagros Basin, SW of Iran) - Hosseini, Seyed Abolfazi (Array, 2008)
Summary: Palaeontological, environmental and sequence stratigraphic studies were carried out on the shallow carbonate platform facies of the Berriasian to Hauterivian Fahliyan Formation and the lower part of the Gadvan Formation, at Kuh-e-Surmeh. The studies were based on calcareous green algae (mainly Dasycladales) and accompanying benthic foraminifera, focusing on revision of the considerable, pioneering work of GOLLESTANEH (1965, 1979), initially undertaken on behalf of the National Iranian Oil Company (NIOC). Thirty two species of calcareous green algae and thirty four species of benthic foraminifera were identifi ed from the Fahliyan Formation and from the lower part of the Gadvan Formation. A number of the recognized calcareous green algae were previously given different names by other authors working in SW Iran. Additional taxa were also recorded for the fi rst time in the Zagros basin, including Clypeina dragastani, C. estevezii, C. solkani, C. parasolkani, Holosporella arabica, Otternstella lemmensis, Salpingoporella circassa, S. istriana and S. katzeri. Salpingoporella circassa is quite common and apparently recorded for the fi rst time from Southern Tethys. Also Salpingoporella? inopinata n. sp., (originally named Iranella inopinata by GOLLESTANEH, a nomen nudum) appears to be quite common in the Fahliyan Formation, although apparently endemic to SW Iran. Three main depositional environments were recognized based on the faunal/fl oral association, lithological and sedimentological characteristics: inner ramp/restricted platform, mid ramp/margin to open platform, and outer ramp/platform slope, with water depths ranging from about 5m to 20m, rarely reaching 40m. Facies changes facilitated the recognition of three large scale sequences throughout the studied succession, bringing interesting relationships with the sequence bundles identifi ed in the Arabian Plate